Factors Affecting Nurses for Doing Therapeutic Communication Therapy to Clients at Mon Geudong Puskesmas Lhokseumawe - Dedy Ahmady; Luqman (Akademi Keperawatan Kesdam Iskandar Muda Lhokseumawe, 2021)
Therapeutic communication is a verbal exchange that is consciously planned, purposeful, and that activities are centered on the healing of the client. The objective of this study is to describe the factors that influence nurses to communicate therapeutically to clients at the Mon Geudong Public Health Center, Lhokseumawe City. This is analytic research with a cross-sectional design. The Respondents in this study amounted to 43 civil servant nurses (total sample). The results obtained between the factors that influence therapeutic communication from 43 respondents, 29 respondents (67.4%) are in the